Economic Impact of NMMO Pretreatment on Ethanol and Biogas Production from Pinewood. (7th September 2014) - Shafiei, Marzieh; Karimi, Keikhosro; Zilouei, Hamid; Taherzadeh, Mohammad J.
Abstract : Processes for ethanol and biogas (scenario 1) and biomethane (scenario 2) production from pinewood improved by N-methylmorpholine-N-oxide (NMMO) pretreatment were developed and simulated by Aspen plus. These processes were compared with two processes using steam explosion instead of NMMO pretreatment ethanol (scenario 3) and biomethane (scenario 4) production, and the economies of all processes were evaluated by Aspen Process Economic Analyzer. Gasoline equivalent prices of the products including 25% value added tax (VAT) and selling and distribution expenses for scenarios 1 to 4 were, respectively, 1.40, 1.20, 1.24, and 1.04 € /l, which are lower than gasoline price. The profitability indexes for scenarios 1 to 4 were 1.14, 0.93, 1.16, and 0.96, respectively. Despite the lower manufacturing costs of biomethane, the profitability indexes of these processes were lower than those of the bioethanol processes, because of higher capital requirements. The results showed that taxing rule is an effective parameter on the economy of the biofuels. The gasoline equivalent prices of the biofuels were 15–37% lower than gasoline; however, 37% of the gasoline price contributes to energy and carbon dioxide tax which are not included in the prices of biofuels based on the Swedish taxation rules.